2019
DOI: 10.1007/s11457-019-09233-0
|View full text |Cite|
|
Sign up to set email alerts
|

Finite Element Analysis of Shell-First and Longitudinally Reinforced Frame-Based Wooden Ships

Abstract: During the period between the 5th century BC and the 6th century AD, two ship construction technologies were prevalent around the Mediterranean Sea: shell-first and framebased. The shell-first concept was of a strong rigid hull, comprising edge-joined strakes reinforced by transverse frames which were not joined to the keel. In the frame-based technique, transverse frames were connected to the keel to form the skeleton, and the strakes were then nailed to the frames. The hull was strengthened with longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…While the structural analysis lacks both precision and the data required for the potential repetition of the analysis, the approach to the problem was consistent, and the study conclusions indicate a consistent and significant advantage of the shell-first method over the frame-based method. Additional details about the aforementioned analysis are provided in the following paper by Helfman et al [45]. Here, three critical interdependent factors are studied: the number of transverse frames, the number of longitudinal reinforcements and their relative location.…”
Section: Strength Of Wooden Structures and Structural Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the structural analysis lacks both precision and the data required for the potential repetition of the analysis, the approach to the problem was consistent, and the study conclusions indicate a consistent and significant advantage of the shell-first method over the frame-based method. Additional details about the aforementioned analysis are provided in the following paper by Helfman et al [45]. Here, three critical interdependent factors are studied: the number of transverse frames, the number of longitudinal reinforcements and their relative location.…”
Section: Strength Of Wooden Structures and Structural Detailsmentioning
confidence: 99%
“…Three main ship hull reinforcement schemes were examined and the corresponding rigidity was determined, as shown in Figure 16. It has been shown that the insertion Additional details about the aforementioned analysis are provided in the following paper by Helfman et al [45]. Here, three critical interdependent factors are studied: the number of transverse frames, the number of longitudinal reinforcements and their relative location.…”
Section: Strength Of Wooden Structures and Structural Detailsmentioning
confidence: 99%